2023
DOI: 10.3389/fphys.2023.1126777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise of different intensities on withdrawal symptoms among people with substance use disorder: a systematic review and meta-analysis

Abstract: Background: Exercise can effectively attenuate withdrawal symptoms and reduce relapse, but it is unknown whether exercise of different intensities produces different results. This study aimed to systematically review the effects of different exercise intensities on withdrawal symptoms among people with substance use disorder (SUD).Methods: Systematic searches for randomized controlled trials (RCTs) on exercise, SUD, and abstinence symptoms were conducted via electronic databases, including PubMed, up to June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…A previous systematic review from Piché et al (2023) has suggested that most common physical activity intervention during SUD treatment identified was of moderate intensity, 3 times per week (≈ 1 h) for 13 weeks, leads to a similar conclusion of the present study. Another meta-analysis on the effects of exercise of different intensities on withdrawal symptoms among people with SUD indicated that different intensity exercise reduced depression after the intervention with moderate-intensity exercise producing the best effect, while only light-and moderate-intensity exercise relieved anxiety (Li et al, 2023). Although this meta-analysis discussed the effects of exercise of different intensities, it did not consider the duration, frequency, type, or period of the exercise interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review from Piché et al (2023) has suggested that most common physical activity intervention during SUD treatment identified was of moderate intensity, 3 times per week (≈ 1 h) for 13 weeks, leads to a similar conclusion of the present study. Another meta-analysis on the effects of exercise of different intensities on withdrawal symptoms among people with SUD indicated that different intensity exercise reduced depression after the intervention with moderate-intensity exercise producing the best effect, while only light-and moderate-intensity exercise relieved anxiety (Li et al, 2023). Although this meta-analysis discussed the effects of exercise of different intensities, it did not consider the duration, frequency, type, or period of the exercise interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that exercising at higher (self-reported) intensities leads to important physiological changes that more effectively decrease anxiety than lower intensity exercise, which, in turn, reduces craving more. For example, a recent review highlighted the plausible role of both exercise effects on the activation of dopamine neurons in the ventral tegmental area and exercise-intensity dependent changes in endocannabinoid signaling in withdrawal symptoms, including anxiety and depressive symptoms, among people with substance use disorder (Li et al, 2023). Consistent with the current findings, previous acute exercise studies have shown that short durations (e.g., 10–20 min) of exercise are associated with improvements in mood states and state anxiety (Brown et al, 2016; Herring et al, 2017).…”
Section: Discussionmentioning
confidence: 99%